PENGARUH KEPEMILIKAN KELUARGA TERHADAP AGRESIVITAS PAJAK DENGAN KUALITAS AUDIT SEBAGAI PEMODERASI - Christa, Ronaldo Geovanda; Adi, Priyo Hari (JEM17: Jurnal Ekonomi Manajemen, 2020)
Tax are considered as expense incurred by the company, this causes the company tends to act aggressively towards taxes. The purpose of this study was to determinate how the influence of family ownership on tax aggressiveness with audit quality as a moderating factor in manufactruring companies listed on the Indonesia Stock Exchange in 2013-2016. The sample used in this study were 244, selceted using the purposive sample method. The data analysis technique used in this study is moderated regression analysis (MRA). The results showed that family ownership affects the tax aggressiveness. Audit quality cannot moderate the effect of family ownership on tax aggressiveness. This means that the higher family ownership of a company, the lower the effective tax rate. Families have a concern with the risks arising from tax aggresiveness.Kata Kunci : Family ownership, Tax Aggresiveness, Audit Quality.